Preparation and characterization of CZTS target and thin film using multi-stage hot-pressing process and pulsed laser deposition. (November 2018) - Su, Cherng-Yuh; Kuo, Ting-Wei; Chen, Po-Chun; Chiu, Yu-Chih; Lin, Pin-Chen; Chang, Chung-Chieh
Abstract: Cu2 ZnSnS4 (CZTS) is a promising material for cost-effective thin film solar cells since its suitable band gap energy and large absorption coefficient in visible light region. In this study, we develop a multi-stage hot-pressing process to make a CZTS target, and conduct a pulsed laser deposition to prepare the CZTS thin film. The CZTS target and thin films have been studied to evaluate their properties as an absorption material for the thin film solar cells. Images and composition analysis from electron probe X-ray micro analyzer confirm the porosity and atomic composition of the hot-pressed CZTS target. The X-ray diffraction pattern indicates a better crystallinity of CZTS thin film after annealing at a higher temperature. Analysis from UV–vis spectroscopy on the annealed CZTS thin films suggests a large absorption coefficient in the visible light region and a band gap energy of 1.45 eV.